2000
DOI: 10.1021/jo9917644
|View full text |Cite
|
Sign up to set email alerts
|

Novel Preparation of α,β-Unsaturated Aldehydes. Benzeneselenolate Promotes Elimination of HBr from α-Bromoacetals

Abstract: Acetalization, alpha-bromination, nucleophilic phenylselenenylation, oxidative elimination/hydrolysis was investigated as a novel protocol for the alpha,beta-dehydrogenation of aldehydes. Treatment of acetals with bromine in methylene chloride afforded the corresponding alpha-bromoacetals in 80-90% yields. Nucleophilic phenylselenenylation was then conveniently effected by treatment with benzeneselenolate generated in situ in dimethyl sulfoxide from diphenyl diselenide, hydrazine and potassium carbonate. Unbra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 45 publications
2
4
1
Order By: Relevance
“…The crude product was purified by column chromatography (pentane/ethyl acetate 99:1) to give 4 as a colorless oil (1.5 g, 75%). 1 H and 13 C NMR data were in agreement with those in the literature. , ESI-MS (70 eV), m / z (%) 154 (1) (M + ), 139 (9), 111 (12), 97 (35), 84 (100), 69 (27).…”
Section: Experimental Proceduressupporting
confidence: 89%
See 1 more Smart Citation
“…The crude product was purified by column chromatography (pentane/ethyl acetate 99:1) to give 4 as a colorless oil (1.5 g, 75%). 1 H and 13 C NMR data were in agreement with those in the literature. , ESI-MS (70 eV), m / z (%) 154 (1) (M + ), 139 (9), 111 (12), 97 (35), 84 (100), 69 (27).…”
Section: Experimental Proceduressupporting
confidence: 89%
“…1 H and 13 C NMR data were in agreement with those in the literature. 36,37 ESI-MS (70 eV), m/z (%) 154 (1) (M + ), 139 (9), 111 (12), 97 (35), 84 (100), 69 (27).…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
“…The signals for the C=O groups in the maleimide repeat unit shifted from 173.2 to 168.6 ppm due to the formation of electron rich carbon-carbon double bond adjacent to C=O after oxidation. However, the reaction efficiency of such a reaction in the current case was lower than those found in the literature [33,34]. However, the current results clearly demonstrated that the phenylselenide substitution could be partial oxidative cleavage from maleimide by 30% H 2 O 2 , which resulted in the introducing of carbon-carbon double bonds in the backbone of copolymer.…”
Section: Resultscontrasting
confidence: 70%
“…The oxidative elimination of selenide moieties is one of the well-known reactions for selenium-containing compounds [32,33]. Herein, the obtained copolymer ([St] 0 /[MSM] 0 /[CPDN] 0 /[AIBN] 0 = 200/200/2/1, precipitated in methanol, M n = 4600 g/mol, Ð = 1.47) was treated with hydrogen peroxide (H 2 O 2 , 30%).…”
Section: Resultsmentioning
confidence: 99%
“…The protected variant of sugar 5 was synthesized from 2-benzyloxy-5,6-dihydro-2 H -pyran ( 18 ), which originated from 3,4-dihydro-2 H -pyran ( 17 ), by treatment with phenylselenium chloride and benzyl alcohol, followed by oxidation and elimination (Scheme ). , The resulting olefin was oxidized with osmium tetroxide to furnish diol 19 . In the case of bleomycin and novobiocin, the pyranose moiety contains a carbamate in lieu of the free alcohols.…”
Section: Resultsmentioning
confidence: 99%